Enhancing problem-solving and collaborative skills through RICOSRE learning model: A socioscientific approach in physics education - Rahma Diani; Bambang Sri Anggoro; Eny Retno Suryani (CV. FOUNDAE, 2023)
Background: Problem-based learning fosters critical thinking by requiring students to analyze information, evaluate solutions, and make well-judged decisions, thereby enhancing their problem-solving skills.Aim: The study aims to assess the impact of the RICOSRE learning model, which is based on socioscientific issues, on students' problem-solving and collaboration skills.Method: Quasi-experimental research was used in this research involving students in classes XI MIPA 2 and XI MIPA 3. Purposive random sampling was used to select participants. Data were collected using test and non-test instruments: essay questions assessed problem solving skills, while questionnaires measured collaboration skills. Hypothesis testing was carried out using Multivariate of Variance (MANOVA).Results:Â The RICOSRE learning model based on socioscientific issues can influence the problem-solving ability and collaboration skills of students, as evidenced by the MANOVA test's significant value (0.000). It was also observed that students with higher levels of collaboration tend to have stronger problem-solving capabilities, suggesting a proportional relationship between these two skills. Notably, students in the experimental class who exhibited outstanding collaborative abilities also showed a high problem-solving rate of 80.67 percent.Conclusion: The study concludes that the RICOSRE learning model, when combined with the Discovery Learning model and a scientific approach, positively influences students' problem-solving and collaboration skills. This model provides an effective learning strategy, enhancing students' ability to apply theoretical concepts to real-world scenarios, thereby making learning more engaging and relevant. Additionally, it prepares students for teamwork, improving their communication and interpersonal skills.